COVID-19, the Climate, and Transformative Change: Comparing the Social Anatomies of Crises and their Regulatory Responses - Rolf Lidskog (Sustainability, 2020)
Despite forces struggling to reduce global warming growing stronger, there has been mixed success in generating substantive policy implementation, while the global spread of the coronavirus has prompted strong and far-reaching governmental responses around the world. This paper addresses the complex and partly contradictory responses to these two crises, investigating their social anatomies. Using temporality, spatiality, and epistemic authority as the main conceptual vehicles, the two crises are systematically compared. Despite sharing a number of similarities, the most striking difference between the two crises is the urgency of action to counter the rapid spread of the pandemic as compared to the slow and meager action to mitigate longstanding, well-documented, and accelerating climate change. Although the tide now seems to have turned towards a quick and massive effort to restore the status quo—including attempts to restart the existing economic growth models, which imply an obvious risk for substantially increasing CO₂ emissions—the article finally points at some signs of an opening window of opportunity for green growth and degrowth initiatives. However, these signs have to be realistically interpreted in relation to the broader context of power relations in terms of governance configurations and regulatory strategies worldwide at different levels of society.